Effectuation and the influence of social networks on the internationalization of accelerated startups - Carolaine Fabricia Bonk Sarmento; Carlos Augusto Septimio de Carvalho; Luis Antonio da Rocha Dib (Internext: Revista Eletrônica de Negócios Internacionais, 2016)
Accelerators recently became a more active alternative to incubators as a mechanism for supporting and developing technology-based startups, especially in their internationalization. At the same time, social networks enable and increase the speed of the process of small firms' internationalization by allowing the attainment of third-party resources and market knowledge. The objective of this research was to better understand how accelerators speed up the process of internationalization for incubated startups. A single case study was conducted on an internet startup. Analysis of the company's internationalization process was based on the theoretical approach of international entrepreneurship and effectuation theory. The results indicated that the startup benefited from resources and knowledge obtained through accelerators that would usually be obtained through a social network. In addition to the accelerator, by replacing informal social networks with more formal and structured ones, the firm was able to increase the speed of internationalization. The main contribution of this article is to illuminate and detail the connection between the theoretical principles of effectuation and the use of social networks in the internationalization of small firms.